SURVIVAL AND GROWT RATE OF SEED SEA CUCUMBER (Holothuria atra) RESULTED BY ASEXUAL REPRODUCTION IN DIFFERENT WEIGHT - Robiansyah, Yani; Nurliah, Nurliah; Hilyana, Sitti (Jurnal Perikanan Unram, 2018)
Fission is an asexual reproductive system of the sea cucumbers (Holothuria atra) by dividing body parts that can form new individuals. This system can be used as an alternative to enchance the sea cucumber individuals. The purpose of this study was to determine the effect of differences in sea cucumber body weight on sea cucumber survival and growth rates based on the results of fission. This study used a complete randomized design and control treatment (150-350 grams / without fission), P1 (150 grams), P2 (250 grams), and P3 (350 grams). Each treatment was repeated six times to obtain 24 experimental units. The analysis test data used ANOVA with a level of 5% to find out the best treatment. Based on the results of the study, it showed the differences in the body weight of the sea cucumbers which influence the survival rate. However, it did not give growth to sea cucumber seeds as a result of fission. There was the highest of survival that obtained from the control treatment (100%) and P2 (72.22%). Then, for the morphological and physiological observations of the sea cucumbers gave different results every week.